Dysregulation of CITED2 in abnormal lung development in the nitrofen rat model - Jank, Marietta; Schwartz, Jacquelyn; Miyake, Yuichiro; Ozturk Aptekmann, Arzu; Patel, Daywin; Boettcher, Michael; Keijzer, Richard (Pediatric surgery international, 2024)
Purpose CITED2 both modulates lung, heart and diaphragm development. The role of CITED2 in the pathogenesis of congenital diaphragmatic hernia (CDH) is unknown. We aimed to study CITED2 during abnormal lung development in the nitrofen model. Methods Timed-pregnant rats were given nitrofen on embryonic day (E) 9 to induce CDH. Fetal lungs were harvested on E15, 18 and 21. We performed RT-qPCR, RNAscope™ in situ hybridization and immunofluorescence staining for CITED2. Results We observed no difference in RT-qPCR (control: 1.09 ± 0.22 and nitrofen: 0.95 ± 0.18, p = 0.64) and in situ hybridization (1.03 ± 0.03; 1.04 ± 0.03, p = 0.97) for CITED2 expression in E15 nitrofen and control pups. At E18, CITED2 expression was reduced in in situ hybridization of nitrofen lungs (1.47 ± 0.05; 1.14 ± 0.07, p = 0.0006), but not altered in RT-qPCR (1.04 ± 0.16; 0.81 ± 0.13, p = 0.33). In E21 nitrofen lungs, CITED2 RNA expression was increased in RT-qPCR (1.04 ± 0.11; 1.52 ± 0.17, p = 0.03) and in situ hybridization (1.08 ± 0.07, 1.29 ± 0.04, p = 0.02). CITED2 protein abundance was higher in immunofluorescence staining of E21 nitrofen lungs (2.96 × 109 ± 0.13 × 109; 4.82 × 109 ± 0.25 × 109, p < 0.0001). Conclusion Our data suggest that dysregulation of CITED2 contributes to abnormal lung development of CDH, as demonstrated by the distinct spatial-temporal distribution in nitrofen-induced lungs.